BOTULINUM TOXIN IN THE MANAGEMENT OF BRUXISM: A COMPREHENSIVE REVIEW - Joanna Węgrzecka,; Klaudia Bilińska,; Tytus Tyralik,; Maciej Karwat,; Paulina Gajniak,; Aleksandra Winsyk,; Kinga Knutelska,; Natalia Kulicka,; Monika Czekalska,; Patrycja Jędrzejewska- Rzezak, (International Journal of Innovative Technologies in Social Science, 2025)
Bruxism, characterized by involuntary grinding or clenching of the teeth, can lead to significant dental, muscular, and psychosocial consequences. Traditional management strategies, including occlusal splints and behavioral therapies, often show variable efficacy. Recently, botulinum toxin (BTX) has emerged as a promising alternative for controlling masticatory muscle hyperactivity. This review examines current evidence on the mechanisms, clinical efficacy, safety, and protocols associated with botulinum toxin use in bruxism treatment. The findings suggest that botulinum toxin offers a minimally invasive, effective, and safe approach, particularly in cases refractory to conventional therapies. Nonetheless, standardization of treatment protocols and long-term safety data remain areas for further research.